'Come and See the Blood in the Streets': Luciano Berio, 'Coro', and the Affective Staging of the One-Crowd. Issue 4 (26th October 2019) - Davis, James
Abstract: Luciano Berio's most substantial work from the 1970s was Coro (1976)—an hour-long piece for chorus and orchestra. This work has attracted a small literature that attempts to understand it in terms of the philosophical framework of the French theorists Gilles Deleuze and Félix Guattari. These Deleuzo-Guattari speculations have remained rather abstract; specifically, they have not attempted to relate the work to the concrete political context of 1970s Italy. This essay attempts to enrich our understanding of Berio by relating the choral work to this political context. In so doing, it will contribute towards a more thorough understanding of the political significance and functioning of the works of one of Italy's leading composers, and suggest a striking political alignment between his musical production and the radical extra-parliamentary political activity of the 1970s.